Pengidentifikasian Dan Pengkreasian Aposisi Pada Komentar Haters Di Media Sosial Sebagai Inovasi Bahan Ajar Bahasa Indonesia Di Smp Kelas VII - Qudhori, Laila; , Drs. Agus Budi Wahyudi, M.Hum (2017)
The method used in this research is qualitative descriptive with syntax study. Technique of data collecting is done by two way that is technique of recall and technique of note. Data analysis technique used is the method of agih with advanced technique of sisip technique and change technique. The result of this research are (1) social media social media haters comment there is aposition statement, pposition statement found some form that is total data amount there are 30 data. The classification according to their espective groups consists of four forms, namely (a) a substitute S of another, 12, (b) a single aposition statement, as much as 14, (c) a multistage form of the stratified apposition, as much as 2, and (d) The substitution of S element with another name and the addition of a single aposition statement as much as 2. (2) The result of this research is an aposition comment which explains S with a negative aposition statement, is made into a positive aposition statement to explain S. (3) On the material Teaching, the use of aposition information is used as an innovative teaching material in writing descriptive responsive text in giving exposure to S or O. Keyword: Syntax, Information apposition, and Social media.